A Comprehensive Paper for Performance Evaluation Between DSDV & AODV Routing Protocol (International Journal of Engineering and Computer Science, 2013)
Ad-hoc networking is a concept in computer communications, which means that users want to communicate with each other form a temporary network, without any form of centralized administration. Each node participating in the network acts both as host and a router and must therefore be willing to forward packets for other nodes. For this purpose, a routing protocol is needed. An ad-hoc network has certain characteristics, which imposes new demands on the routing protocol. The most important characteristic is the dynamic topology, which is a consequence of node mobility. Nodes can change position quite frequently, which means that we need a routing protocol that quickly adapts to topology changes. The nodes in an ad-hoc network can consist of laptops and personal digital assistants and are often very limited in resources such as CPU capacity, storage capacity, battery power and bandwidth. This means that the routing protocol should try to minimize control traffic, such as periodic update messages. Instead the routing protocol should be reactive, thus only calculate routes upon receiving a specific request. In this paper we focus the DSDV and AODV routing protocol with various constraints like packet delivery ratio , end to end to delay etc.